Czech version of the CLASS questionnaire designed for measuring novice-to-expert-like perceptions about biology - Janštová, Vanda; Dvořáková, Radka Marta; Mourek, Jan; Rajsiglová, Ina; Novotný, Petr (Scientia in educatione, 2022)
We contribute to possibilities of quantifying shifts in pupils’ and students’ attitudes toward the field of science, specifically biology, and present the Czech translation of the Colorado Learning Attitudes about Science Survey modified for biology (CLASSBio). In addition to quantifying the attitudes, the survey also includes the expression of the degree of expertise, understood as a percentage of agreement in the answers of a respondent with the answers of experts in the given scientific discipline. Having translated the original English version, adapted it to Czech circumstances and discussed its merits within the group of authors and a native speaker, we piloted the Czech version on 198 respondents. We adjusted partial formulation ambiguities and the final version was used on another 184 respondents. Both surveys were conducted online on applicants for the study of biology at the Faculty of Science, Charles University. The degree of agreement with experts was the same for both genders (approximately 78%), a positive dependence between the achieved score in a biology knowledge test and the degree of agreement with experts was significant, although weak. We confirmed the expected dimensionality of the instrument in the Czech environment by confirmatory factor analysis. The result is a translation of an established tool that enables internationally comparable analyzes.